To go or not to go with the flow: Hawking radiation at strong coupling - Jorge E. Santos (Journal of High Energy Physics, 2020)
Abstract We construct the gravitational dual of a one-parameter class of states of strongly coupled SU(N) N $$ \mathcal{N} $$ = 4 SYM at infinite N and asymptotic temperature T ∞, on a fixed Schwarzschild black hole background with temperature T BH. The resulting bulk geometry is of the flowing type and allow us to measure Hawking radiation at strong coupling. The outgoing Hawking flux is a function of the dimensionless ratio τ ≡ T ∞ /T BH and appears to be non-monotonic in τ. At present, we have no field theory understanding for this behaviour.